2001
DOI: 10.1111/1468-005x.00086
|View full text |Cite
|
Sign up to set email alerts
|

ERP‐Supported Teamworking in Danish Manufacturing?

Abstract: Enterprise Resource Planning (ERP) systems and teamworking both entail significant changes to work on the shopfloor. However, a study of 24 Danish manufacturing enterprises found both change programs were rarely explicitly tuned to each other, with little direct interaction in a majority of cases. A case study shows the importance of, and the micropolitical difficulties involved in getting companies to configure ERP-systems to support teamworking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…Koch and Buhl's (2001) study of 24 cases using ERP as well as self-managing teams, which are a hallmark example of a decentralized organizational approach, can serve to underpin this statement. In all, but one case, both changes were not aligned and initiated separately.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koch and Buhl's (2001) study of 24 cases using ERP as well as self-managing teams, which are a hallmark example of a decentralized organizational approach, can serve to underpin this statement. In all, but one case, both changes were not aligned and initiated separately.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another example of ambivalent and unintended effects of ERP implementation is presented by Koch and Buhl (2001). They present an example of self-managing teams and ERP-systems: the former are an exponent of an organizational decentralization policy, whilst the latter entail centralization of information and therefore often decision-making powers.…”
Section: Job Content and Erp-systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their study of the influence of ERP upon team working, Koch and Buhl [2001] found that team working, across departments, was not reinforced though ERP adoption. Against this backdrop we were keen to revisit this relationship, in the context of ERP adoption amongst Chinese manufacturing companies.…”
Section: The Impact Of Erp / Strategy Upon Horizontal Integrationmentioning
confidence: 97%
“…Moreover, 70% of ERP implementations did not meet the expected benefits [11]. In fact, an ERP project not only has a tendency to become costly to implement but also involves a productivity stemming from disruptions in operations and conflicts among individuals within the organizations [12][13][14]. Despite the documentation on both sides, one set espouses the benefits of a successful implementation and the other discusses the costly risks associated with the poor implementation of an ERP system…”
Section: Introductionmentioning
confidence: 99%